Reductive site-selective atypical C,Z-type/N2-C2 cleavage allows C-terminal protein amidation - Mollner, TA; Giltrap, AM; Zeng, Y; Demyanenko, Y; Buchanan, C; Oehlrich, D; Baldwin, AJ; Anthony, DC; Mohammed, S; Davis, BG (American Association for the Advancement of Science, 2022)
Biomolecule environments can enhance chemistries with the potential to mediate and modulate self-modification (e.g., self-cleavage). While these enhanced modes are found in certain biomolecules (e.g., RNA ribozymes), it is more rare in proteins. Targeted proteolytic cleavage is vital to physiology, biotechnology, and even emerging therapy. Yet, purely chemically induced methods for the site-selective cleavage of proteins remain scarce. Here, as a proof of principle, we designed and tested a system intended to combine protein-enhanced chemistry with tag modification to enable synthetic reductive protein chemistries promoted by diboron. This reductively driven, single-electron chemistry now enables an operationally simple, site-selective cleavage protocol for proteins directed to readily accessible dehydroalanine (Dha) residues as tags under aqueous conditions and in cell lysates. In this way, a mild, efficient, enzyme-free method now allows not only precise chemical proteolysis but also simultaneous use in the removal of affinity tags and/or protein-terminus editing to create altered N- and C-termini such as protein amidation (─CONH2).